The Impact of Social Value Orientation on Pro-environmental Behavior - Yanuvianti, Milda; Srisayekti, Wilis; Fitriana, Efi (Global Medical & Health Communication (GMHC), 2024)
Promoting pro-environmental behavior is a significant concern nowadays. Researchers have identified social value orientation as one of the key factors influencing pro-environmental behavior. This study aims to investigate the influence of social value orientation on pro-environmental behavior and to highlight differences based on gender. The research method used is non-experimental quantitative causality. This research was carried out in 2024 at B University in Bandung. The study participants were 378 students from B University in Bandung, selected using convenience sampling. The measurement tools used were the Triple Dominance Scale by Van Lange (1998) to assess social value orientation (SVO) tendencies and the GEB Scale by Kaiser (2020) to measure general ecological behavior, i.e., the tendency to engage in pro-environmental or non-pro-environmental behavior. Data analysis was done using JASP version 19. The results showed a significant influence of social value orientation on pro-environmental behavior with Fisher's exact test p=0.017 (p<0.05). An odds ratio of 0.084 was obtained, indicating that participants categorized as pro-social are 11.9 times more likely to engage in pro-environmental behavior than those classified as pro-self. Regarding gender differences, the chi-square test revealed no significant differences between males and females in terms of social value orientation tendencies with χ2=0.056 (p>0.05), as well as in terms of engaging in pro-environmental behavior, with χ2=0.774 (p>0.05). The conclusions of this study are that social value orientation affects pro-environmental behavior, and there was no significant difference between gender in social value orientation tendencies and pro-environmental behavior.